Intradiscal injection of oxygen-ozone and intraforaminal steroid for the treatment of prolapsed intervertebral disc: 4 years follow up - Karnalkar, Asmita; Karnalkar, Pratap (International Journal of Research in Medical Sciences, 2017)
Background: Intradiscal injection of Oxygen-Ozone (O2-O3) and intraforaminal steroid is a minimaliy invasive procedure for treatment of low back pain due to prolapsed intervertebral disc. About 9 out of 10 adults experience at least one episode of low back pain at some point in their lifetime. It has been studied that intradiscal and intraforaminal injection of mixture of O2-O3 and steroid produces good outcome than steroid only in such patients. The aim of the study was to evaluate long term therapeutic outcome of Intradiscal injection of Oxygen-Ozone (O2-O3) and intraforaminal steroid in Indian population. Methods: There were 98 patients who were treated with intradiscal injection of O2-O3 and intraforaminal steroid 4 years’ back. All of them had clinical signs of lumbar nerve root compression along with CT and/or MR evidence of contained disk herniation. Eighty two patients were available for follow- up at 4 years. Retrospective study was carried out in those patients. All patients received about 3.5 to 4.0 ml of intradiscal O2- O3 mixture at concentration of 20-24- microgram/ml and intraforaminal injection of 40 mg of inj. Trimnicelone along with 2ml of local anesthetic. Clinical outcome after the injection was assessed by Modified MacNab method and the success of treatment was assessed by means of a visual analog pain scale and the Oswestry Disability Index. Results: A significant reduction in the VAS was observed after 6 weeks and 6 months (from 8.6 to 5.4 and 6.0; p<0.001) in all patients; an excellent therapy response (VAS below 3.0) was achieved at 4 years. A significant improvement in ODI was registered in all patients (36 to 14.8; p < 0.001). Patients below 50 years had significantly better values in the VAS and the ODI score 4 years after treatment. Final VAS and ODI scores for patients with a single diseased segment were 4.2 and 28.0. The total effective rate according to Modified MacNab method (excellent and good /fair) was 93.9% at end of 6 months, 97.55% at 1 year and 4 years it was 97.55%. No patient was operated for spine surgery. Conclusions: Intradiscal injection of O2-O3 and intraforaminal steroid is highly effective in relieving lower back pain in patients with lumbar disc herniation not responding to conservative therapy. There was significant clinical outcome even after 4 years.